A plasma synthesis method for rapidly constructing multi-level micro-nanostructured perovskite catalysts

The treatment of perovskite catalysts through sliding arc discharge plasma technology solves the problem of high phase temperature and high active sites in traditional methods, and achieves the formation of high specific surface area and high active sites, which significantly improves catalytic activity and preparation efficiency.

CN119771512APending Publication Date: 2025-04-08SHANWEI YUXIN CHANGHENG ENVIRONMENTAL TECHNOLOGY CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411968555.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The high phase formation temperature of existing perovskite catalysts makes it difficult to obtain high specific surface area and high active sites, limiting their catalytic activity and general use.

Method used

The sliding arc discharge plasma technology is adopted to replace the calcination treatment in the traditional template method, and the rapid construction of perovskite catalysts and the formation of multi-stage micro-nano structures are achieved.

Benefits of technology

This method can remove template agents and other impurities in a short time, forming perovskite catalysts with high specific surface area and high active sites, significantly improving catalytic activity and preparation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219287320000061
    Figure BDA0005219287320000061
  • Figure BDA0005219287320000071
    Figure BDA0005219287320000071
  • Figure BDA0005219287320000081
    Figure BDA0005219287320000081
Patent Text Reader

Abstract

The present application discloses a plasma synthesis method for rapidly constructing a multi-level micro-nano structured perovskite catalyst, belonging to the fields of plasma preparation technology and catalyst synthesis technology. The plasma synthesis method of the present application adopts sliding arc discharge plasma to replace the calcination treatment adopted by the traditional template method for preparing perovskite catalysts. Through the sliding arc discharge plasma treatment, the complexing agent, surface dispersant and template agent are quickly removed to obtain a perovskite phase catalyst with a regular multi-level micro-nano structure, which greatly shortens the preparation cycle. With the help of the high activity and high temperature characteristics of the sliding arc discharge plasma, a perfect perovskite crystal phase and a large number of highly active catalytic sites are obtained. At the same time, the problems of high phase formation temperature of perovskite catalysts, difficulty in removing template agents, small specific surface area and difficulty in constructing catalytically active structures are solved, and the synthetic preparation process is more convenient and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a plasma synthesis method for rapidly constructing a multi-level micro-nanostructured perovskite catalyst, belonging to the field of plasma preparation technology and catalyst synthesis technology. Background Art

[0002] ABX3-type perovskite catalysts have the advantages of low price, flexible electronic structure, and high stability, and can be widely used in environmental protection, energy conversion and other fields. However, the phase formation temperature of conventional perovskite catalysts is relatively high, and it is difficult to obtain high specific surface area (usually less than 10m2) during high-temperature synthesis. 2 / g), which greatly limits the catalytic activity of the catalytic material, thereby affecting its promotion and use. In order to increase the surface area of ​​the perovskite catalyst, a template method can be used to construct a perovskite porous material. However, the use of the traditional template method to prepare the perovskite catalyst requires the template agent after impregnation to be calcined to obtain a porous structure. This process is not only long in cycle (generally requires calcination for more than 4 hours), but also the long high-temperature phase formation process is difficult to obtain highly active catalytic active sites (mainly composed of oxygen vacancies). For example, the patent with publication number CN105668647A discloses a high specific surface area perovskite nano LaCoO3 porous hollow sphere material and its preparation method. The dark brown powder must be placed in a muffle furnace, first heated at 300-400°C for 4 hours, and then heated to 700-800°C for 4 hours.

[0003] Plasma discharge treatment technology can generate non-equilibrium plasma under normal pressure. It has the advantages of high reaction activity, rapid startup, and simple equipment. It shows great potential in the field of catalyst synthesis and preparation. For example, the patent with publication number CN118899455A discloses a platinum-cobalt alloy catalyst and its plasma treatment method and application. The inventor modified the surface of the platinum-cobalt alloy catalyst by plasma treatment. The temperature of the treatment process is not higher than 100°C, and the number of active sites of the catalyst is significantly increased under this low temperature characteristic; however, this low temperature and high activity condition is not applicable to the synthesis and preparation of the catalyst. In fact, because dielectric barrier discharge (DBD) plasma is often used in catalyst synthesis, preparation and treatment, it is difficult to remove difficult-to-decompose precursors at a low temperature, and the effect is not ideal in preparing catalysts with high phase temperature and high precursor stability. Summary of the invention

[0004] In order to solve the problems of long cycle and difficulty in obtaining high active sites in the prior art of high specific surface area perovskite preparation, this application proposes a technical solution for the rapid construction of ion synthesis of multi-level micro-nanostructured perovskite catalysts, replacing the traditional template method for preparing perovskite catalyst calcination treatment, thereby solving the problem of long preparation cycle and difficulty in obtaining highly active catalytic active sites. The sliding arc discharge used in this application can simultaneously meet the phase formation temperature of the perovskite catalyst, the oxidative removal of the template agent, and the construction of high-activity catalytic active sites on the surface (mainly relying on the rapid surface action of active species in plasma at higher temperatures), and the processing process is more convenient.

[0005] This application adopts the following technical solutions:

[0006] According to the first aspect of the present application, a plasma synthesis method for rapidly constructing a multi-level micro-nanostructured perovskite catalyst is provided, comprising the following steps:

[0007] S1, providing a metal salt precursor solution of perovskite;

[0008] S2, impregnating the template into the metal salt precursor solution, then adding a complexing agent and a surface dispersant to the metal salt precursor solution, stirring, and separating to obtain a solid product;

[0009] S3, placing the solid product in a sliding arc discharge plasma region for sliding arc discharge plasma treatment to obtain the multi-level micro-nanostructure perovskite catalyst.

[0010] Optionally, the process of placing the solid product in a gliding arc discharge plasma region for treatment can quickly remove the complexing agent, surface dispersant and template agent.

[0011] Optionally, in step S3, the conditions of the sliding arc discharge plasma region include: a temperature of 700 to 1000° C., a discharge power of 40 to 100 W, and a flow rate of the working gas of 2 to 10 L / min.

[0012] Optionally, the working gas is selected from one of an oxidizing atmosphere, a reducing atmosphere, and a neutral atmosphere. The working gas of the gliding arc discharge plasma is selected according to the composition of the processed perovskite catalyst.

[0013] Optionally, in step S3, the sliding arc discharge plasma treatment is performed for 10 to 30 minutes.

[0014] Optionally, in step S3, the sliding arc discharge plasma region is provided by a reactor selected from the group consisting of a pneumatic sliding arc discharge reactor, a magnetically driven sliding arc discharge reactor, and a cyclone sliding arc discharge reactor.

[0015] Optionally, the power supply of the reactor is one of a direct current power supply, a pulse power supply and an alternating current power supply.

[0016] Optionally, the pulse time of the pulse power supply is 2 to 10 ns.

[0017] Optionally, the frequency of the AC power supply is 50 Hz to 30 kHz.

[0018] Optionally, in step S1, the perovskite is a metal oxide with a molecular formula of ABX3;

[0019] A is a rare earth or alkaline earth metal element, B is a transition metal element or a noble metal element, and X is an oxygen element or a halogen.

[0020] Optionally, in step S1, the metal salt precursor solution includes a soluble metal salt of A, a soluble metal salt of B, and a solvent.

[0021] Optionally, in step S1, the molar ratio of element A to element B in the metal salt precursor solution is 1:1.

[0022] Optionally, in step S1, the soluble metal salt of A is selected from at least one of nitrate, acetate, sulfate or halide of A.

[0023] Optionally, in step S1, the soluble metal salt of B is selected from at least one of nitrate, acetate, sulfate or halide of B.

[0024] Optionally, in step S1, the solvent is selected from at least one of water and alcohol.

[0025] Optionally, in step S1, in the metal salt precursor solution, the concentration of the soluble metal salt of A is 0.1 to 10 mol / L, calculated on the basis of the molar content of the element A.

[0026] Optionally, in step S2, the template is selected from a hard template and / or a soft template;

[0027] The template comprises at least two pore structures of micropores, mesopores and macropores.

[0028] Optionally, the template is selected from activated carbon and PMMA.

[0029] In the present application, the template is a material having a rich pore structure and can be removed by oxidation or high temperature.

[0030] Optionally, in step S2, the complexing agent is selected from at least one of citric acid and EDTA.

[0031] Optionally, in step S2, the surface dispersant is selected from at least one of an amine salt and a quaternary ammonium salt.

[0032] Optionally, in step S2, the molar ratio of the total amount of the complexing agent and the surface dispersant to the total amount of elements A and B in the metal salt precursor solution is 0.8 to 1.6:1.

[0033] Optionally, the molar ratio of the complexing agent to the surface dispersant is 1:0.6-1.4.

[0034] Optionally, the molar ratio of the template to the total amount of elements A and B in the metal salt precursor solution is 0.5 to 2:1.

[0035] Optionally, in step S2, the stirring time is 1 to 2 hours;

[0036] Optionally, in step S2, the separation is performed by centrifugation for 2 to 3 times.

[0037] Optionally, step S2 further includes drying the solid product;

[0038] The drying conditions include: drying at a temperature of 50 to 120° C. for 4 to 16 hours.

[0039] Optionally, the drying method is selected from vacuum drying.

[0040] The beneficial effects of this application include:

[0041] (1) The present application uses the sliding arc discharge plasma technology to prepare a perovskite catalyst with a multi-porous structure, which can simultaneously meet the requirements of effective removal of the template, perfect phase formation of the catalyst, and construction of highly active catalytic active sites on the surface.

[0042] (2) In the preparation of multi-level micro-nanostructured perovskite catalysts, the present application uses sliding arc discharge plasma technology to replace the calcination treatment used in the traditional template method, which is more convenient, has a faster processing speed, and has a larger specific surface area of ​​the catalyst.

[0043] (3) The catalyst preparation of the present invention is completed rapidly at a high temperature, and the template agent is efficiently removed without causing collapse of the pore structure, making the catalyst structure more stable.

[0044] (4) The present application adopts discharge-generated plasma treatment to prepare perovskite catalysts. The discharge atmosphere is flexible and adjustable. While constructing the catalyst structure, the redox properties of its surface can also be effectively adjusted, making it easy to customize sites with high catalytic activity.

[0045] (5) The plasma treatment process of the present application can be started and stopped quickly, has high process energy efficiency, a short preparation cycle, and rarely produces secondary pollutants at high temperatures, making the preparation process more environmentally friendly. DETAILED DESCRIPTION

[0046] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0047] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0048] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0049] The PMMA template used in the examples of the present application was prepared by the Stober-Frink method, and the specific steps are as follows:

[0050] a. Take a 2000ml three-necked flask, install a condenser at the top of the three-necked flask, and two ports on the left and right sides, one of which is for inert gas, and the other is plugged for adding reactants later. Add 850ml of deionized water to the three-necked flask, pass inert gas, and stir steadily in a water bath at 80℃ for 30min;

[0051] b. Take two 50ml beakers, add 1.8g KPS initiator and 30ml deionized water to one beaker, stir at 80℃ for 20min; add 20ml deionized water to the other beaker, stir at 80℃ for 20min;

[0052] c. Take 100 ml of MMA (methyl methacrylate) monomer and add it into a 2000 ml three-necked flask through the port with a stopper, then add the KPS solution stabilized at 80°C into the three-necked flask through the same port, and wash the KPS beaker with 20 ml of deionized water in another beaker and add it into the three-necked flask. After reacting at 80°C for 30 minutes, pour it into a large beaker filled with 1000 ml of deionized water and mix to obtain a PMMA microsphere emulsion;

[0053] d. Centrifuge the PMMA microsphere emulsion at 6000 rpm for about 90 minutes, precipitate the supernatant with a pipette, transfer the remaining white sample in the centrifuge tube to a beaker, weigh its mass, and then add deionized water to prepare an emulsion with about 20 wt% PMMA. Disperse the emulsion by ultrasonic for 60-90 minutes until the emulsion is uniform, and obtain a PMMA self-assembly template emulsion;

[0054] e. Take an appropriate amount of PMMA self-assembly template emulsion into a flat-bottom container and evaporate the water in a 60°C water bath to promote the self-assembly of PMMA microspheres. After the water is completely evaporated, the self-made PMMA template agent is obtained.

[0055] The source of the ordered mesoporous carbon template used in the examples of the present application is: small-particle nanoporous carbon powder NCP-15-1 produced by Nanjing Jicang Nanotechnology Co., Ltd.

[0056] Example 1

[0057] Follow the steps below:

[0058] a. Take 32.49 g of La(NO3)3 and 18.29 g of Co(NO3)2, dissolve them in 100 mL of deionized water and stir to obtain a metal salt precursor solution;

[0059] b. Weigh 15 ml of the metal salt precursor solution obtained in step a, impregnate it on 2 g of PMMA template, add 2.88 g of citric acid complexing agent, 1.61 g of ammonium nitrate surface dispersant, stir for 90 min, then centrifuge at 20000 r / min, centrifuge twice, each time for 1 h, and separate to obtain a solid sample;

[0060] c. The solid sample obtained in step b is placed in an oven at 100°C and dried for 8 hours, and then placed in a pneumatic sliding arc discharge reactor. The preparation temperature (>800°C) is controlled by adjusting the position of the catalyst zone in the reactor. Sliding arc discharge is performed in an air atmosphere with a gas flow rate of 3L / min. The power supply of the discharge reactor is a 15kHz AC power supply with an input power of 80W. After 10 minutes of sliding arc discharge plasma treatment, a LaCoO3 catalyst with a multi-level micro-nano structure can be obtained.

[0061] Comparative Example 1

[0062] Follow the steps below:

[0063] a. Take 32.49 g of La(NO3)3 and 18.29 g of Co(NO3)2, dissolve them in 100 mL of deionized water and stir to obtain a metal salt precursor solution;

[0064] b. Weigh 15 ml of the metal salt precursor solution obtained in step a, impregnate it on 2 g of PMMA template, add 2.88 g of citric acid complexing agent, 1.61 g of ammonium nitrate surface dispersant, stir for 90 min, then centrifuge at 20000 r / min, centrifuge twice, each time for 1 h, and separate to obtain a solid sample;

[0065] c. The solid sample obtained in step b was placed in an oven and dried at 100°C for 8 hours. The dried solid sample was then placed in a muffle furnace, heated at 400°C for 4 hours, then heated to 750°C and calcined for 4 hours, and finally naturally cooled to room temperature to obtain a LaCoO3 catalyst with a multi-level micro-nano structure.

[0066] As a comparative study, the LaCoO3 catalyst obtained by the sliding arc discharge plasma treatment and the LaCoO3 catalyst obtained by the calcination treatment were subjected to the methane dry reforming reaction by increasing the temperature from 500°C to 750°C, and the conversion rates of reactants CH4 and CO2 obtained by the LaCoO3 catalyst obtained by the sliding arc discharge plasma treatment and the LaCoO3 catalyst obtained by the calcination treatment at different temperatures were compared. As shown in Table 1, for the LaCoO3 catalyst obtained by the sliding arc discharge plasma treatment, as the reaction temperature increased from 500°C to 750°C, the conversion rates of CH4 and CO2 increased from 22.4% and 25.3% to 78.6% and 73.7%, respectively, while the conversion rates of CH4 and CO2 of the LaCoO3 catalyst obtained by the calcination treatment increased from 16.5% and 18.6% to 63.3% and 61.9%, respectively. It can be seen that at the same reaction temperature, the CH4 and CO2 conversion rates of the LaCoO3 catalyst obtained by sliding arc discharge plasma treatment were significantly higher than those of the LaCoO3 catalyst obtained by calcination treatment, which indicates that the LaCoO3 catalyst obtained by sliding arc discharge plasma treatment exhibits higher catalytic activity.

[0067] Table 1 Comparative data on the methane dry reforming reaction effects of LaCoO3 catalysts obtained by gas-driven gliding arc discharge plasma treatment and LaCoO3 catalysts obtained by calcination

[0068]

[0069]

[0070] Example 2

[0071] Follow the steps below:

[0072] a. Take 29.59 g of Ti(NO3)4 and 21.16 g of Sr(NO3)2, dissolve them in 100 mL of deionized water and stir to obtain a metal salt precursor solution;

[0073] b. Weigh 20 ml of the metal salt precursor solution obtained in step a, impregnate it on 3 g of the ordered mesoporous carbon template, add 5.84 g of EDTA complexing agent, 1.61 g of ammonium nitrate surface dispersant, stir for 100 min, then centrifuge at 15000 r / min, centrifuge twice, each time for 1.5 h, and separate to obtain a solid sample;

[0074] c. The solid sample obtained in step b is placed in an oven at 80°C and dried for 10 hours, and then placed in a magnetically driven sliding arc discharge reactor. The preparation temperature (>700°C) is controlled by adjusting the position of the catalyst zone in the reactor. An argon atmosphere sliding arc discharge is used with a gas flow rate of 1L / min. The power supply of the discharge reactor is a 20kHz AC power supply with an input power of 100W. After a magnetically driven sliding arc discharge plasma treatment for 10 minutes, a SrTiO3 catalyst with a multi-level micro-nano structure can be obtained.

[0075] Comparative Example 2

[0076] Follow the steps below:

[0077] a. Take 29.59 g of Ti(NO3)4 and 21.16 g of Sr(NO3)2, dissolve them in 100 mL of deionized water and stir to obtain a metal salt precursor solution;

[0078] b. Weigh 20 ml of the metal salt precursor solution obtained in step a, impregnate it on 3 g of the ordered mesoporous carbon template, add 5.84 g of EDTA complexing agent, 1.61 g of ammonium nitrate surface dispersant, stir for 100 min, then centrifuge at 15000 r / min, centrifuge twice, each time for 1.5 h, and separate to obtain a solid sample;

[0079] c. The solid sample obtained in step b was placed in an oven and dried at 80°C for 10 hours. The dried solid sample was then placed in a muffle furnace, heated at 350°C for 3 hours, then heated to 800°C and calcined for 4 hours. Finally, it was naturally cooled to room temperature to obtain a SrTiO3 catalyst with a multi-level micro-nano structure.

[0080] The SrTiO3 catalyst obtained by magnetically driven sliding arc discharge plasma treatment and the SrTiO3 catalyst obtained by calcination treatment were respectively combined with a flat-plate dielectric barrier discharge reactor to form a plasma catalytic system, and were used to treat toluene of the same concentration for oxidation removal. During the experiment, the total gas flow rate was kept at 300mL / min, the initial concentration of toluene gas was 650ppm, and the plasma input power was 7W. The results are shown in Table 2. The plasma catalytic system constructed by the SrTiO3 catalyst obtained by magnetically driven sliding arc discharge plasma treatment can achieve a toluene conversion rate and CO2 selectivity of 79% and 67% for typical indoor VOCs pollutants, respectively, and the concentration of the secondary pollutant O3 generated by the discharge is 13mg / m 3 Under the same conditions, the plasma catalytic system constructed using the calcined TiSrO3 catalyst also has the ability to remove toluene, but the effect is not very good (toluene conversion, CO2 selectivity and O3 concentration are 61%, 52% and 37mg / m 3It can be seen that under the same conditions, the plasma catalytic system constructed by the SrTiO3 catalyst obtained by magnetic-driven sliding arc discharge plasma treatment is better than the plasma catalytic system constructed by the SrTiO3 catalyst obtained by calcination treatment in treating the typical indoor VOCs pollutant toluene.

[0081] Table 2 is a comparative data on the removal effect of toluene pollutants by the plasma catalytic system constructed based on SrTiO3 catalysts obtained by dielectric barrier discharge, magnetic driven sliding arc discharge plasma treatment and calcination treatment.

[0082]

[0083] Example 3

[0084] Follow the steps below:

[0085] a. Dissolve 32.49 g of La(NO3)3, 17.89 g of Mn(NO3)2, and 31.91 g of Pt(NO3)2 in 90 mL of deionized water and stir to obtain a metal salt precursor solution;

[0086] b. Weigh 15 ml of the metal salt precursor solution obtained in step a, impregnate it on 2 g of the ordered mesoporous carbon template, add 4.87 g of EDTA complexing agent, 1.33 g of ammonium nitrate surface dispersant, stir for 80 min, then centrifuge at 2500 r / min, centrifuge twice, each time for 2 h, and separate to obtain a solid sample;

[0087] c. The solid sample obtained in step b is placed in an oven at 120°C and dried for 6 hours, and then placed in a cyclone sliding arc discharge reactor. The preparation temperature (>750°C) is controlled by adjusting the position of the catalyst zone in the reactor. H2 atmosphere sliding arc discharge is used with a gas flow rate of 4L / min. The power supply of the discharge reactor is a 10kHz AC power supply with an input power of 80W. After cyclone sliding arc discharge plasma treatment for 15 minutes, a Pt@LaMnO3 perovskite catalyst with Pt nanoparticles uniformly dispersed on the surface of the multi-level micro-nano structure can be obtained.

[0088] Comparative Example 3

[0089] Follow the steps below:

[0090] a. Dissolve 32.49 g of La(NO3)3, 17.89 g of Mn(NO3)2, and 31.91 g of Pt(NO3)2 in 90 mL of deionized water and stir to obtain a metal salt precursor solution;

[0091] b. Weigh 15 ml of the metal salt precursor solution obtained in step a, impregnate it on 2 g of the ordered mesoporous carbon template, add 4.87 g of EDTA complexing agent, 1.33 g of ammonium nitrate surface dispersant, stir for 80 min, then centrifuge at 2500 r / min, centrifuge twice, each time for 2 h, and separate to obtain a solid sample;

[0092] c. The solid sample obtained in step b was placed in an oven at 120°C and dried for 6 hours, and then the dried solid sample was placed in a muffle furnace, heated to 700°C and calcined for 6 hours, and finally naturally cooled to room temperature to obtain a LaMnO3 perovskite skeleton with a multi-level micro-nano structure;

[0093] d. H2 high temperature reduction treatment step c obtained LaMnO3 perovskite skeleton for 45min, gas flow rate of 1100mL / min, discharge reactor input power of 90W, and obtained Pt@LaMnO3 perovskite catalyst with Pt nanoparticles uniformly dispersed on the surface of multi-level micro-nano structure.

[0094] As a comparative study, the Pt@LaMnO3 catalyst obtained by cyclone sliding arc discharge plasma treatment and the Pt@LaMnO3 catalyst obtained by high temperature reduction treatment catalyzed the water vapor change reaction. It can be found from Table 3 that when the reaction temperature is from 140℃ to 200℃, the CO conversion rate of the Pt@LaMnO3 catalyst obtained by cyclone sliding arc discharge plasma treatment ranges from 63% to 99%; while for the Pt@LaMnO3 catalyst obtained by high temperature reduction treatment, the CO conversion rate ranges from 39% to 86%. Under the same conditions, the low-temperature catalytic performance of the Pt@LaMnO3 catalyst obtained by cyclone sliding arc discharge plasma treatment is better than that of the Pt@LaMnO3 catalyst obtained by high temperature reduction treatment in catalyzing the water vapor shift reaction.

[0095] Table 3 Comparison of the catalytic effects of Pt@LaMnO3 catalysts obtained by cyclonic sliding arc discharge plasma treatment and Pt@LaMnO3 catalysts obtained by high temperature reduction treatment on the water vapor change reaction

[0096]

[0097] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A plasma synthesis method for rapidly constructing a multi-level micro-nanostructured perovskite catalyst, characterized in that: The steps include: S1, providing a metal salt precursor solution of perovskite; S2, impregnating the template into the metal salt precursor solution, then adding a complexing agent and a surface dispersant to the metal salt precursor solution, stirring, and separating to obtain a solid product; S3, placing the solid product in a sliding arc discharge plasma region for sliding arc discharge plasma treatment to obtain the multi-level micro-nanostructure perovskite catalyst.

2. The plasma synthesis method according to claim 1, characterized in that: In step S3, the conditions of the sliding arc discharge plasma region include: a temperature of 700 to 1000° C., a discharge power of 40 to 100 W, and a flow rate of the working gas of 2 to 10 L / min; Preferably, the working gas is selected from one of an oxidizing atmosphere, a reducing atmosphere and a neutral atmosphere.

3. The plasma synthesis method according to claim 2, characterized in that: In step S3, the time of the sliding arc discharge plasma treatment is 10 to 30 minutes.

4. The plasma synthesis method according to claim 1, characterized in that: In step S3, the sliding arc discharge plasma region is provided by a reactor selected from the group consisting of a pneumatic sliding arc discharge reactor, a magnetically driven sliding arc discharge reactor, and a cyclone sliding arc discharge reactor; Preferably, the power supply of the reactor is one of a direct current power supply, a pulse power supply and an alternating current power supply.

5. The plasma synthesis method according to claim 1, characterized in that: In step S1, the perovskite is a metal oxide with a molecular formula of ABX3; A is a rare earth or alkaline earth metal element, B is a transition metal element or a noble metal element, and X is an oxygen element or a halogen.

6. The plasma synthesis method according to claim 5, characterized in that: In step S1, the metal salt precursor solution includes a soluble metal salt of A, a soluble metal salt of B, and a solvent.

7. The plasma synthesis method according to claim 6, characterized in that: In step S1, in the metal salt precursor solution, the concentration of the soluble metal salt of A is 0.1 to 10 mol / L, based on the molar content of the element A.

8. The plasma synthesis method according to claim 1, characterized in that: In step S2, the template is selected from a hard template and / or a soft template; The template comprises at least two pore structures of micropores, mesopores and macropores; Preferably, in step S2, the complexing agent is selected from at least one of citric acid and EDTA; Preferably, in step S2, the surface dispersant is selected from at least one of an amine salt and a quaternary ammonium salt.

9. The plasma synthesis method according to claim 1, characterized in that: In step S2, the molar ratio of the total amount of the complexing agent and the surface dispersant to the total amount of the A and B elements in the metal salt precursor solution is 0.8 to 1.6:1; Preferably, the molar ratio of the complexing agent to the surface dispersant is 1:0.6-1.4; Preferably, the weight ratio of the template to the total amount of elements A and B in the metal salt precursor solution is 0.5 to 2:

1.

10. The plasma synthesis method according to claim 1, characterized in that: In step S2, the stirring time is 1 to 2 hours; Preferably, step S2 further comprises drying the solid product; The drying conditions include: drying at a temperature of 50 to 120° C. for 4 to 16 hours.

Citation Information

Patent Citations

  • High-specific surface area perovskite nano-LaCoO3 porous hollow sphere material and preparation method thereof

    CN105668647A

  • Platinum-cobalt alloy catalyst and plasma treatment method and application thereof

    CN118899455A